PENTINGNYA MEDIA PEMBELAJARAN KREATIF UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK SDN 1 BLANGKEJEREN - Fitriani, Ria (CULTURAL EDUCATION JOURNAL OF LITERATURE AND CULTURE, 2023)
School is a place for students to gain knowledge. However, it is not uncommon for us to encounter students who lack interest in carrying out the learning process and seem to be ignorant of the material presented by the teacher during the learning process and feel bored to participate in the entire series of learning activities in the classroom so that the learning objectives are not achieved optimally, so that a teacher need to conduct self-evaluation and improve the quality of learning in the classroom. In this case, improving the quality of learning in the classroom can be done in various ways and teachers have a very important role in increasing students' interest in learning so that students feel comfortable, happy and the knowledge they gain will be easy for them to accept. This study aims to analyze the use of learning media in increasing students' learning interest. The research method used in this study is the method of observation through direct interviews. The object of this research is to use 5 relevant journals whose variables correspond to the research title. Learning media has an important role to increase the learning interest of elementary school students, especially in lower grades, because low grade students are not yet able to think abstractly, so the material taught by the teacher needs to be visualized in a more concrete/real form. It can be concluded that the use of media in the learning process can have implications for three things, including the teacher, the students and the learning process.